“Inhuman Acts of Lesbian Love” : The Lesbian Stigmatization Process from Weimar Germany to KZ Ravensbrück - Iannucci, Giulia (My University, 2021)
This paper investigates the extent of the presence of lesbians in Germany between the end of the Weimar Republic and the sedimentation of Nazism, notably focusing on the dialectical perception between negation and (in)visibility that characterizes the stigmatization process undergone by the lesbian prisoners in KZ Ravensbrück, the only concentration camp entirely for women. During the “Golden Twenties”, the absence of female homosexuality in law was incongruous with the real presence of lesbianism within Weimar society, culture, and art. Following Adolf Hitler’s rise to power, while female homosexuality remained uncriminalized, lesbians began being persecuted in “unorthodox” ways and interned in concentration camps. Lesbians were detained on the grounds that they were considered asozial (“anti-social”). Consequently, lesbianism was contextualized within a new (forgotten) environment in which the role of women was manipulated by a patriarchal system aimed at standardizing, normalizing, and repressing the “lives unworthy of life”, most of which still remain invisible.
Keywords: Lesben; Nationalsozialismus; Stigmatisierung; 943 Geschichte Mitteleuropas; Deutschlands; Lesbische Liebe; Weimarer Republik; Ravensbrück